PELATIHAN PEMROGRAMAN BERORIENTASI OBJEK SEBAGAI UPAYA PENGUATAN KETERAMPILAN CODING MAHASISWA - Rezki Wulandari; Zila Razilu; Rahmawati Rahmawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Coding skills have become a crucial competency for Information Technology Education (ITE) students in the era of Industrial Revolution 4.0 and Society 5.0. However, ITE students at Muhammadiyah University of Kendari still face difficulties in understanding and applying Object-Oriented Programming (OOP) concepts, particularly abstract paradigms such as encapsulation, inheritance, and polymorphism. This research aims to evaluate the effectiveness of OOP training in enhancing students' coding skills. The research method employed a descriptive qualitative approach involving 45 students who participated in online training for 2 hours via teleconference on November 14, 2025. Data were collected through pre-tests and post-tests, participation observation, coding implementation evaluation, and identification of learning obstacles. The results showed a significant improvement with the average score increasing from 52.8 to 78.4 (48.5% improvement). The participation rate reached 90% with 84.4% of students completing the exercises. Students successfully mastered basic concepts such as class creation (93.3%) and encapsulation (84.4%), but still required reinforcement in inheritance (68.9%) and polymorphism (53.3%). The main obstacles included unstable internet connection (17.8%) and difficulty focusing on online learning (26.7%). The conclusion of this research is that OOP training proved effective in improving students' conceptual understanding and coding skills, thus it needs to be integrated as a continuous reinforcement program in the ITE curriculum.